Gender Differences of Gly972Arg Polymorphism of the IRS-1 Gene Related to Cardiovascular Disease Risk Factors Among Indonesians - Renan Sukmawan; Harry Mahathir Akip; Priyandini Wulandari; Evans T Bobians; BRM Ario Soeryo Koencoro; Siska Suridanda Danny; Ade Meidian Ambari; Sunu Budhi Raharjo; Bambang Widyantoro; Suko Adiarto (Interna Publishing, 2023)
Background: Cardiovascular disease is driven by traditional risk factors, sex, and genetic differences. The Asian population, specifically Indonesians, has been known at high risk of insulin resistance and endothelial dysfunction. A possible genetic risk factor related to cardiovascular diseases is Gly972Arg polymorphism of insulin receptor substrate 1 (IRS-1) gene, as this impairs endothelial function. To date, whether there is a gender difference in Gly972Arg polymorphism of the IRS-1 gene in Indonesians is unknown. This study aimed to to define whether there is a gender difference in Gly972Arg polymorphism of the IRS-1 gene in Indonesians. Methods: We studied adults living in two areas (rural and urban) in Indonesia. We collected demographic and clinical data from the study subjects. Gly972Arg polymorphism of the IRS-1 gene (rs1801278) was detected using TaqMan real-time polymerase chain reaction. Results: A total of 378 subjects were recruited. The wild-type allele (CC) was found in 86 (22.8%) subjects, heterozygous mutant allele (CT) in 245 (64.8%), and homozygous mutant allele in 47 (12.4%). The proportion of subjects with T alleles was significantly higher among women than men (54.6% vs. 45.4%, odds ratio: 1.89; p = 0.01). Subjects with T allele more often have hypertension (odds ratio: 1.69, p = 0.058). Conclusion: There were a higher proportion of women than men carrying the T allele of Gly972Arg polymorphism among Indonesians. Individuals with the T allele appeared to show a greater prevalence of hypertension. These results may explain a possible mechanism of the high prevalence of metabolic syndrome in Indonesia, especially in women.